Vocational Education and Training: Discourse, Systems, and Practices of VET in Rural Tasmania and Nova Scotia - Corbett, Michael; Ackerson, Zachary (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
In this article we offer a comparative analysis of vocational education and training (VET) in two rural regional locations by situating the pragmatic problem of advising rural students against the backdrop of differently structured market-oriented vocational education systems in Canada and Australia, respectively. Each of these jurisdictions offers a particular vision of the place of VET in the context of compulsory education. In rural/regional Canada and Australia, we argue, the socio-material situation within which students live can provide what Bourdieu called “coherent and convenient” educational choices for students to challenge educators to create the conditions for an engaging and non-binary (academic-vocational) approach to compulsory schooling. We conclude, given the constantly changing nature of contemporary occupational opportunities and labour markets, that the goals of the new vocationalism will only be achieved in rural areas through challenging programming that focuses on capabilities, change, and multiple integrated literacies that span and expand the academic-vocational binary.